Impact of 1p/19q codeletion on the diagnosis and prognosis of different grades of meningioma. (2nd September 2016) - Basaran, Recep; Uslu, Serap; Gucluer, Berrin; Onoz, Mustafa; Isik, Nejat; Tiryaki, Mehmet; Yakicier, Cengiz; Sav, Aydin; Elmaci, Ilhan
Abstract: Background: Meningiomas are one of the most common tumours to affect the central nervous system. Genetic mutations are important in meningeal tumourigenesis, progression and prognosis. In this study, we aimed to examine the effect of 1p/19q deletion on the diagnosis and prognosis of meningioma subtypes using the fluorescence in situ hybridization (FISH) method. Methods: Twenty-four patients with meningioma were retrospectively studied. Tumour samples were obtained from 10 typical, 11 atypical and three anaplastic malignant meningiomas. The most representative tumour sections were screened for 1p/19q deletion using the FISH method. Results: Of the 24 patients, eight were women (33.3%) and 16 (66.7%) were men. The mean age was 56.6 years. The higher-grade meningioma was usually seen in males and had a higher rate of deletion on 1p ( p = 0.001). There was a statistically significant difference between the grades and the rate of deletion on 19q ( p = 0.042) and between the grades and the rates of polysomy, monosomy and amplification on 19q ( p = 0.002; p = 0.001; p = 0.002, respectively). There was no statistical difference between 1p/19q codeletion and the grades of meningioma ( p > 0.05). We detected higher level of Ki-67 in the condition of codeletion but did not find a statistical difference ( p = 0.0553). Conclusion: Deletion on 1p, as well as deletion, polysomy, monosomy and amplification on 19q, are detected more frequently in high grade meningiomas. This amplification is most likely due to the amplification of oncogenes.